Catheter‐directed thrombolysis for submassive pulmonary embolism in children: A case series. Issue 4 (25th December 2019) - Belsky, Jennifer; Warren, Patrick; Stanek, Joseph; Kumar, Riten
Abstract: Incidence of venous thromboembolism, including pulmonary embolism (PE), continues to rise in children. Optimum management of submassive PE is unclear. The principal objective of this retrospective study was to investigate the radiological and clinical outcomes in children with submassive PE treated with catheter‐directed thrombolysis (CDT). Five patients underwent six episodes of CDT. No patient developed major/clinically relevant non‐major bleeding. Most patients had complete radiological thrombus resolution and no patient had evidence of chronic thromboembolic pulmonary hypertension. There is an urgent need for larger prospective cohort studies/randomized controlled trials to investigate the role of CDT in pediatric PE.